(untitled) (Research, Society and Development, 2022)
Histoplasma is a pathogenic fungus that causes histoplasmosis, an endemic systemic mycosis due to the occurrence/positivity in specific regions. The virulence of this fungus has been revealed in recent years, aided by the techniques of functional gene characterization, which use gene inactivation, by deletion, or decrease in the production of gene products. Molecular tools for gene transformation, such as Agrobacterium-mediated transformations (ATMT), which favor the formation of RNA interference, have ensured the expansion of knowledge about virulence mechanisms implemented by different pathogenic microorganisms, such as H. capsulatum. In ATMT, a DNA fragment is introduced into the target cell when the bacterium is stimulated by chemical signals. DNA integrates into the genome and provides gene silencing via RNAi, a method of reducing the gene product, due to mRNA degradation, through the formation or introduction of a double-stranded RNA molecule into the target host, which are abhorred by cells eukaryotic. For Histoplasma, the ability of double-stranded RNAs, introduced by the ATMT technique, to trigger depletion of many target genes has been widely demonstrated, and so far has favored a better understanding of the metabolic flexibility of this pathogen.